Main Engine Water Cooling Failure Monitoring and Detection on Ships using Interface Modbus Communication - Dwi Sasmita Aji Pambudi; Ruddianto; Anggara Trisna Nugraha Angga; Agung Prasetyo Utomo; Mahasin Maulana Ahmad; Mayda Zita Aliem Tiwana; Alwy Muhammad Ravi (Unusa Press, 2021)
Main engine failure will damage engine systems, reduce navigation safety, and cause serious marine accidents. The cooling system is very important to prevent the engine's mechanical efficiency from deteriorating and engine failure due to overheating. Therefore, a monitoring and error detection system is needed. The system is based on the Modbus RS485 communication and interface. The collection equipment uses components from the 7S-50MC diesel engine. PLC is used as processing equipment and Logic Panel Autonics S070 is used as an interface. Through these tests, error detection in this study can provide an indication of an error when an abnormal situation occurs. In addition, data monitoring and system fault indication can be displayed on the interface. Testing of the system proved that it complies with the Indonesian Shipping Bureau (BKI) regulations on engine warning systems. The research developed can form the basis of more complex and reliable monitoring and fault detection system for applications on ships.